Macrotrabecular Hepatocellular Carcinoma: An Aggressive Subtype of Hepatocellular Carcinoma. (July 2019) - Jeon, Yejoo; Benedict, Mark; Taddei, Tamar; Jain, Dhanpat; Zhang, Xuchen
Abstract : The macrotrabecular (MT) pattern of hepatocellular carcinoma (HCC) has been suggested to represent a distinct HCC subtype. We retrospectively reviewed 231 HCC cases. Detailed pathologic evaluation for histologic patterns, including MT-pattern, was performed for each case and recorded as percentage involved at 10% intervals. MT-pattern was defined as having trabeculae >6 cells thick. After excluding all recognized HCC subtypes, remaining cases were deemed conventional HCC (CV-HCC) and served as controls. HCCs with a component of ≥10%, ≥30% and ≥50% MT-pattern were identified in 41 (17.7%), 24 (10.4%) and 4 (1.7%) cases, respectively. The clinicopathologic features of HCCs with 10% to 29% MT-pattern (n=17, 7.4%) were largely similar to CV-HCC. No significant difference was observed between the 30% and 49% (n=20) and ≥50% (n=4) MT groups, hence these were combined for further analysis as MT-HCC. MT-HCCs (≥30% MT-pattern) were larger tumors (5.5 vs. 3.1 cm), were less likely to be associated with cirrhosis (54% vs. 79%), were more likely to have hepatitis B (21% vs. 5%) and less likely hepatitis C infection (33% vs. 58%) compared with CV-HCC. MT-HCC was associated with the presence of anaplastic tumor cells (42% vs. 14%), higher alpha‐fetoprotein level, higher AJCC stage, and higher histologic grade. Compared with patients with CV-HCC, patients with MT-HCC had poorer overall survival. Patients with MT-HCC who underwent primary resection or transplantation had a higher recurrence rate and worse recurrence-free survival. Our findings suggest that ≥30% MT-pattern could be used as the more appropriate cut-off for defining MT‐HCC, which represents a unique and aggressive HCC histologic subtype.